Optimized Fabrication Of Tio2 Nanotube Arrays By Anodization For Solar Cell Applications - Nyein, Nyein (2017)
TiO2 nanotubes (TNT) arrays have attracted significant attention in solar cell applications: photoelectrochemical cell (PEC) and dye-sensitized solar cell (DSSC) for the production of renewable energy. In this thesis, highly ordered, uniform surface TNT arrays were successfully fabricated by anodization of titanium in ammonium fluoride (NH4F)/ethylene glycol (EG) electrolyte containing alkaline species of LiOH, NaOH or KOH. As a comparison, TNT arrays were also fabricated in H2O/EG under the same condition. The H2O/EG electrolyte resulted in shorter TNTs (10 m) and diameter of 160 nm. This is due to the high chemical etching at the tip of nanotubes, caused by the higher concentration of H+ ions. Alkaline species especially NaOH and KOH added into fluoride/EG electrolytes produced longer tubes with length of 18 and 23 m and a diameter of 160 and 170 nm, respectively. The present of alkaline species increased the electrolyte pH and this can suppress chemical etching process at the top part of nanotubes. However, they do not affect the local acidification inside the nanotubes at the tube bottom that is needed for inwards growth of the tubes. As for the LiOH, it was observed that the salt did not dissolve very well in the electrolyte, hence the length of nanotubes in this electrolyte is only 14 m. As-anodized TNT arrays formed in alkaline species added into fluoride/EG electrolyte have anatase crystallites within them due to the higher content of OH ions. NaOH/EG was acknowledged in this work as the most optimum electrolyte for nanotube formation with considerable length and good surface etching that open up the nanotubes at the top. Studies on the effect of the amount of NaOH, amount of NH4F, applied voltage, anodization time and annealing process were then conducted and it was found that 1 M of NaOH, 0.7 wt % of NH4F, 60 V of applied voltage, 60 min of anodization time and 450 C of annealing process can produce the highest photocurrent of PEC. The TNTs were used as photoanode in both PEC and DSSC. The PEC performance was determined by photocurrent generation of the cell and by solar to hydrogen conversion efficiency (STH). Maximum STH of 4.3 % was achieved from photoanode comprising of 23 m long TNT arrays and a diameter of 175 nm derived in 5 wt % NaOH/EG corresponding to photocurrent of 3.5 mA/cm2. As for the DSSC, it was also found that NaOH/EG sample gave the best performance with photoconversion efficiency () of 3.1 % and a short-circuit current density (Jsc) of 9.1 mA/cm2 as this sample has the longest length, largest aspect ratio, and good anatase crystallinity. This sample was then decorated with silver nanoparticles (Ag NPs) by photodeposition method as to extend absorption of light to the visible region and to reduce the recombination of photogenerated electron/hole pairs. 10-30 nm diameter Ag NPs were formed from 0.2 M Ag-precursor solution and the Ag NPs/TNTs exhibit the highest  of 3.7 % and Jsc of 12.2 mA/cm2 compared to sample without Ag NPs. The increase in photoconversion efficiency was due to the surface plasmon resonance effect and excess electrons from the Ag NPs.